The Visualization Study on the Slug Flow Mechanisms of the Air-Water Two-Phase in a 50 mm Horizontal Pipe - Dinaryanto, Okto; Hudaya, Akhmad Zidni; Deendarlianto, Deendarlianto; Indarto, Indarto (SENATIK STT Adisutjipto, 2018)
The slug flow phenomena are often encountered in various industrial applications such as petroleum, process, and power plant. The presence of slug flow should be avoided as it causes structural damage due to resonance, corrosion and pipes blast. From the view point of multiphase flow, the understanding of the slug initiation mechanism is very important in pipeline design. This research is conducted using horizontal transparent acrylic pipes with diameters of 50 mm with a variation on the superficial velocity of water between 0,1 m/s and 0,77 m/s and superficial velocity of air between 0,31 m/s and 6,2 m/s. In the present experimental study, the slug initiation mechanisms was explained by visual observation by using high speed video cameras. As the results, the slug flow initiation mechanism were clarified. Furthermore, the proposed of flow initiation map was introduced.